Allegory as representation of the other - Vidauskytė, Lina (Religija ir kultūra, 2009)
This article deals with German philosopher’s Walter Benjamin philosophical concept of allegory. The concept of allegory is aplied as method in the main works of Benjamin. This method is concidered as a way of speaking about the Other. Allegory represents Baroque Trauerspiel (it is an autonomous genre rather than continuation of Anciet Tragedy) and have interruption between form and content, meaning and expression. Benjamin seaks the rehabilitation of allegory from its humiliation since Romanticism. Benjamin’s notion of language after the Fall is one of the most important issues for using allegory, or indirect speech. Allegory is nearly the one way of expression in such historical (not mythological) situation. Allegory’s fragmentation, its dialectics of convention and expression, its origin from mourning gaze, formal kinship to such contents as decay and death, its origin from “the Fall of language spirit” etc. are the main characteristics of such philosophical method.
Keywords: allegory; symbol; Baroque; Romanticism; indirect speech; Other; Trauerspiel; truth